Modified Fixed Prosthesis to Rehabilitate Edentulism in Growing Patients: Report of two cases - Paudel, Sushma; Rai, Amita; Shrestha, Sneha; Ghimire, Luna; Poudel, Bishnu; Sundas, Sunanda (Journal of Nepalese Prosthodontic Society, 2025)
Tooth loss in children and adolescents, can lead to difficulty in chewing, change in speech, and compromised esthetics that significantly impacts the overall quality of life. There are limited options available for rehabilitating edentulism in young patients. Modified fixed prosthesis is a transitional fixed prosthesis which is comfortable to the patient, easy to fabricate, cost effective, and it does not interfere with the development of jaw bones and permanent tooth. This case report highlights the provision of modified fixed prosthesis in two young female patients.